Relevance, ad hoc concepts and analogy - Ewa Mioduszewska (LingBaW)
In Relevance Theory (RT) concepts are “enduring elementary mental structure[s] capable of playing different discriminatory or inferential roles on different occasions in an individual’s mental life.” (Sperber & Wilson, 2012, p. 35). They may be lexicalized atomic concepts, ad hoc atomic concepts not encoded in our linguistic system and some innate concepts (Carston, 2010, p. 14). Concepts may be shared between interlocutors, idiosyncratic but grounded in common experience or fully idiosyncratic and non-communicable. They are “arrived at through the mutual pragmatic adjustment of explicature and contextual implicatures.” (Carston, 2010, p. 10). Ad-hoc concepts are “pragmatically derived, generally ineffable, non-lexicalized […] rough indication to aid readers in understanding what we have in mind in particular cases.” (Carston 2010, p. 13). Concepts encoded will only occasionally be the same as the ones communicated because words are used to convey indefinitely many other ad hoc concepts constructed in a given context (Sperber & Wilson, 2012, p. 43). Apparently, RT restricts the construction of ad hoc concepts by the search for relevance (definitions of (optimal) relevance, principles of relevance and relevance-theoretic comprehension procedure) and the potential connection (narrowing or broadening) between the denotations of the encoded and constructed concepts. The mechanisms underlying category narrowing/broadening seem not to be explicitly described and explained. What provides a very general but, at the same time, precise account of concept-relatedness is Hofstadter & Sander’s (2013) understanding of analogy. The question posed here is whether this understanding may help explain concept-relatedness in Relevance Theory.